"The Living Dead". (1st March 2020) - Singh, Ranjit
This paper follows the mutual shaping of data records and citizens as data subjects to illustrate how precarious forms of citizenship emerge in the use of biometrics-based digital technologies for governance. It presents a case of using Aadhaar, India's biometrics-based unique identification project, in the delivery of welfare pensions to the elderly, widows, and the disabled in Rajasthan. In March 2016, pensions of about 757, 000 beneficiaries were cancelled for a variety of reasons ranging from the beneficiary is "dead" or "duplicate" to other ineligibility criteria such as age or income. When Right to Information activists organized public hearings on these cancellations, they found many beneficiaries who were alive but declared "dead" on record. This paper explores this case of the "living dead" to conceptualize orphaning from information infrastructures as processes that render citizens residual in the mutual shaping of their lives with their data records.